Effects of static and dynamic shading on thermodynamic and electrical performance for photovoltaic panels - Bayrak, Fatih; Öztop, Hakan Fehmi (Pergamon-Elsevier Science Ltd, 2020)
An experimental examination has been performed on the performance assessment of different shading shapes on photovoltaic panels by using energy-exergy analysis methods in this study. The problem is important due to decreasing of performance of PV panel with shading effect. A non-transparent material and powder were used for static shading while the time-varying shading effect of a chimney for dynamic shading was applied on to the system. Novelty of the work is to use diagonal shading on energy and exergy efficiency. Moreover, thermal camera technique was used to observe the effects of temperature distribution as a novel technique for PV panels. The photovoltaic panel was kept outside for one month in terms of dusty shading. For other static shading, artificial shadows of three different triangular shapes (40 * 40 cm for Case I, 36 * 60 cm for Case II and 60 * 36 cm for Case III) were created. The energy and exergy efficiencies of all systems under the same solar radiation were compared. The Case I-III under the same solar radiation was imaged by using a thermal camera and the effect of shading on photovoltaic panels and hot spot formation were examined. The results showed that the highest energy efficiency value was found to be 10.54% for the reference panel, 9.70% for the dusty panel, 4.16% for Case I, 4.27% for Case II and approximately zero for Case III. In the panel of dynamic shading, the lowest and the highest efficiency values were found as 0.86% and 10.27%, respectively.
Keywords: Photovoltaic; Partial shading; Temperature; Heat transfer; Efficiency; Thermal imaging